Formulation and evaluation of PVA/PEG peel-off mask containing rich fraction of Centella asiatica and Cucumis sativus extract for anti-ageing - Shafawi, Anis Natasha; Bakhtiar, M. Taher; Darnis, Deny Susanti (2018)
Premature ageing can be seen through the formation of wrinkles and altered pigmentation earlier than it should be. Due to premature ageing and high demand for a mask that can dry faster with easy application, peel-off mask can be used to solve the problems due to its ability to remove dead skin cells and able to treat premature ageing with the addition of active ingredients. Generally, peel-off mask is a gel that is thinly applied on face and can be peeled off as thin film from the face. In this research, the benefits of peel-off mask will be enhanced by the addition of the rich fraction of Centella asiatica (asiaticoside) and Cucumis sativus extract due to their antioxidant properties and collagen-synthesis inducer. Thus, the objectives of this research are to formulate peel-off mask containing the rich fraction of C. asiatica and C. sativus extract and to evaluate the physicochemical properties of peel-off mask formulation. In order to identify the best formulation, the screening test was conducted by using the different concentration of chemical ingredients to obtain the desired properties of peel-off mask formulation. The modified formulation was made up of 20 % of polyvinyl alcohol (PVA) with some additional ingredients which are polyethylene glycol (PEG), glycerine, propylene glycol, ethanol, parabens, citric acid, the rich fraction of C. asiatica and C. sativus extract. The physicochemical properties of this peel-off mask formulation were found to be affected by its storage temperature. Generally, all formulations remained colourless with slight PVA odour. Besides that, they were homogenous with no visible coarse grains. The ranges of spreadability were between 0.47 and 0.77 cm, and they have low drying time which was about five min. The pH values fall within skin pH, which was between 5.74 and 6.19, with viscosity ranges between 0.16 and 0.32 kP. Surface morphology of dried films was affected by the spreadability of the gel, where formulation with ideal spreadability produced the smooth surface. Lastly, this formulation was found to be stable against mold and fungi, but not against bacteria. To conclude, the peel-off mask made up of 20 % of PVA with the rich fraction of C. asiatica and C. sativus extract has good physicochemical properties with good stability at low (8 ± 3 °C) and room temperature (24 ± 3 °C).